Social Justice, Sport and Racism A Position Statement - Love, Adam; Deeb, Alexander; Waller, Steven N. (2019)
Despite common claims that society is “post-racial” and that sport is apolitical, issues of racial injustice continue to permeate sport and recreational institutions. Drawing insight from critical race theory, we articulate a vision of social justice oriented toward illuminating and addressing issues of racial injustice in sport and recreation. In particular, we highlight pressing matters of racial injustice in sport at the elite, competitive levels, as well as community and recreational settings. We also discuss contemporary examples and strategies for resisting racial injustice, noting the challenges and difficulties associated with various approaches. In doing so, we hope to provide direction for scholars and activists in fighting for social justice with respect to racism and racial inequality in sport.
Keywords: Critical Race Theory; Leisure; Recreation; Resistance; Segregation